Initial investigation of Trichogrammatoidea lutea (Hymenoptera: Trichogrammatidae) as biological control agent of codling moth, Cydia pomonella (Lepidoptera: Tortricidae), in apple and pear orchards, under sterile insect technique (SIT) - Wahner, Nadine (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScAgric (Conservation Ecology and Entomology))--Stellenbosch University, 2008.